PEMANFAATAN MEDIA WORDWALL UNTUK MENINGKATKAN KEMAMPUAN MATEMATIKA PADA ANAK USIA 5-6 TAHUN DI TK AL-FATTAH KECAMATAN JAYANTI - Isnaini Zulaiha; Romdoni (LPPM IAD Probolinggo, 2026)
This study aims to determine the use of Wordwall media on the mathematical development of children aged 5–6 years. Aspects studied include the ability to recognize numbers 1–20, add numbers 1–20, and demonstrate number concepts. This study used a descriptive method with 15 children as subjects. Data collection techniques were carried out through observation and documentation with indicators referring to the Child Development Achievement Level Standards (STPPA) according to Permendikbud Number 137 of 2014. The results of the study indicate that the use of Wordwall media has a positive impact on children's mathematical development. Most children have been able to achieve the expected development indicators in the three aspects studied. Wordwall media creates interactive and fun learning that increases children's activeness and understanding. Thus, Wordwall media is effective for stimulating early childhood mathematical development.